Blockchain for business 2019 : a user-friendly introduction to blockchain technology and its business applications - Lipovyanov, Peter (Packt Publishing, 2019)
Blockchain has the potential to change the world and has become the hottest field in the tech sector now. Blockchain for Business is a comprehensive guide that enables you to fully understand the far-reaching applications beyond Bitcoin and empowers you to make fully-informed decisions.